2022
DOI: 10.23975/bjvetr.2022.177459
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Glanders Regarded Iraq and Surrounding Countries

Abstract: Glanders caused by Burkholderia mallei infected mainly the Equidae and it is really fatal zoonosis. It was known since ancient times. The horses, mules, and donkeys can get infection by skin abrasion, and during direct contact between animals or with water instruments, also the bacterium can be found in the soil. Since the disease was eradicated from most of the developed world, Glanders is endemic in several countries surrounding Iraq and other related regions of the middle east. Regardless a limited space of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This study is considered the first work using the PCR technique in Iraq to diagnose glanders disease. The research has previously been diagnosed using serological methods such as ELISA, or diagnosis by using maline test or collecting research on the presence of this disease, A high incidence rate with this microorganism in horses (7,8,17).…”
Section: Total Results Of Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is considered the first work using the PCR technique in Iraq to diagnose glanders disease. The research has previously been diagnosed using serological methods such as ELISA, or diagnosis by using maline test or collecting research on the presence of this disease, A high incidence rate with this microorganism in horses (7,8,17).…”
Section: Total Results Of Pcrmentioning
confidence: 99%
“…A several studies reported incidence of Glanders in Iraq, since 1977 Al-Kafawi, et al, has study about glanders disease, then the researcher in the college of Veterinary Medicine in Baghdad studies disease by the histopathological and electron microscope, recently many studies conducted present glanders in Iraq by using ELISA kit (18,19,8,17).…”
Section: Table (3) Show Results Of Pcr and Comparative Between Male A...mentioning
confidence: 99%